Effects of extraction methods on phenolic content in the young bamboo culm extracts of Bambusa beecheyana Munro - Nuzul, Mohd. Izuddin; Yi, Vivien Yi Mian; Koo, Lee Feng; Chan, Thye Huat; Ang, Chung Huap; Idris, Juferi; Husen, Rafidah; Wong, Siaw Wei (Multidisciplinary Digital Publishing Institute, 2022)
Nowadays, many studies focus on the potential of bamboo as a source of bioactive compounds and natural antioxidants for nutraceutical, pharmaceutical, and food sources. This study is a pioneering effort to determine the total phenolic content, total flavonoid content and free radical scavenging activity, as well as the phenolic identification and quantification of Bambusa beecheyana. The study was conducted by using ethanol, methanol, and water for solvent extraction by applying cold maceration, Soxhlet, and ultrasonic-assisted extraction techniques. The results showed that Soxhlet and ultrasonic-assisted Bambusa beecheyana culm extracts had an increase in the extract’s dry yield (1.13–8.81%) but a constant p-coumaric acid (4) content (0.00035 mg/g) as compared to the extracts from the cold maceration. The ultrasonic-assisted extraction method required only a small amount (250 mL) of solvent to extract the bamboo culms. A significant amount of total phenolics (107.65 ± 0.01 mg GAE/g) and flavonoids (43.89 ± 0.05 mg QE/g) were found in the Soxhlet methanol culm extract. The extract also possessed the most potent antioxidant activity with an IC50 value of 40.43 µg/mL as compared to the positive control, ascorbic acid. The UHPLC–ESI–MS/MS analysis was carried out on the Soxhlet methanol extract, ultrasonic-assisted extract at 40 min, and cold methanol extract. The analysis resulted in the putative identification of a total of five phenolics containing cinnamic acid derivatives. The two cinnamic acid derivatives, p-coumaric acid (4) and 4-methoxycinnamic acid (5), were then used as markers to quantify the concentration of both compounds in all the extracts. Both compounds were not found in the water extracts. These results revealed that the extract from Soxhlet methanol of Bambusa beecheyana could be a potential botanical source of natural antioxidants. This study provides an important chemical composition database for further preclinical research on Bambusa beecheyana.